The Chinese Scholarship on Mongolia and Its Development Trend - Meng, Gencang (Mongolian Journal of International Affairs, 2024)
Since the normalization of the relationship between China and Mongolia in the early 1990s, the Chinese academia has conducted a multi-angle research on Mongolia’s political and economic transformation, foreign policy, and social culture. Especially on the contents of the Belt and Road, since the President of China proposed the China-Mongolia-Russia Economic Corridor in 2014, Chinese universities and research institutions have successively established the Mongolia Research Centers and related research institutions, dedicated to research on the corridor construction, Sino-Mongolian strategic development, humanities exchange, and other related researches. This paper will introduce China’s Mongolia Research Centers and other related research institutions and analyze the Chinese scholarship on Mongolia and its development trend.